Understanding Changes in Poverty - Inchauste, Gabriela; Azevedo, João Pedro; Essama-Nssah, B.; Olivieri, Sergio; Van Nguyen, Trang; Saavedra-Chanduvi, Jaime; Winkler, Hernan (World Bank Group, Washington, DC, 2014)
Understanding Changes in Poverty brings together different methods to decompose the contributions to poverty reduction. A simple approach quantifies the contribution of changes in demographics, employment, earnings, public transfers, and remittances to poverty reduction. A more complex approach quantifies the contributions to poverty reduction from changes in individual and household characteristics, including changes in the sectoral, occupational, and educational structure of the workforce, as well as changes in the returns to individual and household characteristics. Understanding Changes in Poverty implements these approaches and finds that labor income growth that is, growth in income per worker rather than an increase in the number of employed workers was the largest contributor to moderate poverty reduction in 21 countries experiencing substantial reductions in poverty over the past decade. Changes in demographics, public transfers, and remittances helped, but made relatively smaller contributions to poverty reduction. Further decompositions in three countries find that labor income grew mainly because of higher returns to human capital endowments, signaling increases in productivity, higher relative price of labor, or both. Understanding Changes in Poverty will be of particular relevance to development practitioners interested in better understanding distributional changes over time. The methods and tools presented in this book can also be applied to better understand changes in inequality or any other distributional change.